Genetic variation in arsenic (+3 oxidation state) methyltransferase (AS3MT), arsenic metabolism and risk of basal cell carcinoma in a European population. (25th August 2014) - Engström, Karin S.; Vahter, Marie; Fletcher, Tony; Leonardi, Giovanni; Goessler, Walter; Gurzau, Eugen; Koppova, Kvetoslava; Rudnai, Peter; Kumar, Rajiv; Broberg, Karin
<x xml:space="preserve">Abstract</x> Exposure to inorganic arsenic increases the risk of basal cell carcinoma (BCC). Arsenic metabolism is a susceptibility factor for arsenic toxicity, and specific haplotypes in arsenic (+3 oxidation state) methyltransferase (AS3MT) have been associated with increased urinary fractions of the most toxic arsenic metabolite, methylarsonic acid (MMA). The aim of this study is to elucidate the association of AS3MT haplotypes with arsenic metabolism and the risk of BCC. Four AS3MT polymorphisms were genotyped in BCC cases (N = 529) and controls (N = 533) from Eastern Europe with low to moderate arsenic exposure (lifetime average drinking water concentration: 1.3 µg/L, range 0.01–167 µg/L). Urinary metabolites [inorganic arsenic (iAs), MMA, dimethylarsinic acid (DMA)] were analyzed by HPLC‐ICPMS. Five AS3MT haplotypes (based on rs3740400 A/C, rs3740393 G/C, rs11191439 T/C and rs1046778 T/C) had frequencies >5%. Individuals with the CCTC haplotype had lower %iAs (P = 0.032) and %MMA (P = 0.020) in urine, and higher %DMA (P = 0.033); individuals with the CGCT haplotype had higher %MMA (P < 0.001) and lower %DMA (P < 0.001). All haplotypes showed increased risk of BCC with increasing arsenic exposure through drinking water (ORs 1.1–1.4, P values from <0.001 to 0.082), except for the CCTC haplotype (OR 1.0, CI 0.9–1.2, P value 0.85). The results suggest that carriage of AS3MT haplotypes associated with less‐efficient arsenic methylation, or lack of AS3MT haplotypes associated with a more‐efficient arsenic methylation, results in higher risk of arsenic‐related BCC. The fact that AS3MT haplotype status modified arsenic metabolism, and in turn the arsenic‐related BCC risk, supports a causal relationship between low‐level arsenic exposure and BCC. Environ. Mol. Mutagen. 56:60–69, 2015. © 2014 The Authors. Environmental and Molecular Mutagenesis published by Wiley Periodicals, Inc. on behalf of Environmental Mutagen Society